2003
DOI: 10.1007/s00774-003-0435-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound of bone and clodronate effects in thalassemia-induced osteoporosis

Abstract: Osteoporosis in beta-thalassemia major has emerged as a topic of interest since optimized transfusion regimens have increased life expectancy and quality in these patients. Although the pathogenesis of thalassemic osteopathy is multifactorial, the evidence of an increased resorption phase suggests that the use of antiresorptive drugs such as bisphosphonates can be considered a valuable therapeutic strategy to reduce bone turnover and the risk of fragility fractures. We compared the effects of long-term cyclica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 17 publications
1
24
1
7
Order By: Relevance
“…11,12 Our study suggests the potential benefits of BMT in reversing the bone complications in TM. Although several studies reported the usefulness of bisphosphonates in treating bone complications for TM, 20,21 there has not been any report on whether BMD in these patients would improve spontaneously after BMT. Our post transplant TM patients had a significantly lower rate of BMD deficits in their left hips.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Our study suggests the potential benefits of BMT in reversing the bone complications in TM. Although several studies reported the usefulness of bisphosphonates in treating bone complications for TM, 20,21 there has not been any report on whether BMD in these patients would improve spontaneously after BMT. Our post transplant TM patients had a significantly lower rate of BMD deficits in their left hips.…”
Section: Discussionmentioning
confidence: 99%
“…A male patient with thalassemia major with severe marrow expansion of the maxilla doi: 10.1210/er.2015-1105 press.endocrine.org/journal/edrv 17 Treatment with zoledronic acid, alendronate and neridronate was associated with a significant increase in BMD, but clodronate was not associated with a significant increase in BMD despite achieving a significant reduction in bone turnover markers (211). A direct comparison between BMD is not possible in these trials given the different treatment agents and baseline risk of osteoporosis in each study.…”
Section: Medullary Expansionmentioning
confidence: 94%
“…Despite the mean age of study participants being less than 50 years, only one study reported DXA Z scores (210) with the other studies reporting areal BMD and T scores (211)(212)(213)(214). It is also important to stress that the zoledronic acid used in these trials was given at a dose of 4 mg every 3 to 6 months for up to 2 years (212,213) in contrast to the more common dose of 5 mg once a year in the nonthalassemia population.…”
Section: B Bisphosphonatesmentioning
confidence: 98%
“…This is because in patients of TIO, there is an increased bone resorption attributable to an enhanced osteoclastic function [4,8], and bisphosphonates are potent inhibitors of osteoclastic function [9][10][11]. In several previous studies, alendronate, clodronate, pamidronate, and zoledronate have all been examined for their potential use in this regard [12][13][14][15][16][17][18][19][20][21][22][23], and zoledronate has been identified as the most promising candidate bisphosphonate for an additional reason that its dosages can be timed in such a way as to coincide with the transfusion sessions [12]. Yet, the United States Food and Drug Administration have currently placed a safety alert [24,25] on zoledronate due to two possible adverse effects associated with its use: severe musculoskeletal pain and atrial fibrillation [26,27].…”
Section: Introductionmentioning
confidence: 99%